Biophilosophical knowledge through the prism of philosophical-educational approaches - Галина Берегова (Філософія освіти)
The article is devoted to the methodological and methodical function of the philosophy of education regarding the variability of the content of modern philosophical knowledge in higher education. The article argues why biophilosophy, as an educational discipline, can be included in educational and educational-scientific programs as a mandatory or optional component. The relevance of the study of biophilosophy for future generations is also asserted, since biophilosophy is a variant of naturalistically oriented philosophy, the conceptual core of which is life, and the content of biophilosophical knowledge covers the philosophy of biology, the philosophy of life and related axiology. It is determined in the work that biophilosophical knowledge contains a potential opportunity to form a worldview in a person with the prevailing ideas of the value and significance of life, to provide a deep awareness of the unity of man and living nature, and therefore to contribute to the comprehensive disclosure of the epistemological, ontological, methodological and axiological foundations of life, on which life is built biological picture of the world. Biophilosophical cognition is interpreted as an intellectual and mental component of personal knowledge (in particular, knowledge about living things) and becomes the basis and source of further relevant cognitive processes (biological knowledge), which stimulates the humanization of human activity, harmonizes human relationships, and is indirectly manifested in the change of people’s attitude to the surrounding world. The conclusions state that biophilosophy in the system of higher education can be a new worldview paradigm for the preservation of human culture and civilization, provided it is popularized through institutions of higher education. Also, biophilosophy, as an educational discipline and a discipline of the new enlightenment, can successfully fulfill one of the main educational tasks: to form in the minds of young people a modern biological picture of the world and a modern worldview.